A Study on the Elasticity of Time in a Perceived Polychronic Culture - Kenneth Amoah; Esther Gyamfi; Ronald Osei Mensah (Richtmann Publishing, 2023)
This study sought to measure polychronicity in the Ghanaian public sector. A qualitative approach was applied to the data collection. An improved polychronic attitude scale was used as the overall measure of monochronic/polychronic tendencies. This scale had been developed, tested and modified for the management setting to be utilized in measuring departmental or organizational polychronicity. A convenience selection of 30 participants from the Takoradi Technical University was done, and those selected were interviewed, using a semi-structured interview guide. Creswell and Poth’s (2018) Analysis Spiral Plan used was to handle the data, and the findings showed a disposition towards monochronic behavior. There was evidence of generally positive results when the impact of the polychronicity of the participants was evaluated, although participants exhibiting monochronic tendencies benefited the most. All the participants, irrespective of their polychronicity inclination, demonstrated that their time use preference helped them get work done. Again, their communication context aided them to achieve their communication objective. Also, the managements of public sector organizations, knowing the monochronic tendencies of their administators should strategize and implement policies such as polychronic superiors being tolerant with their surbordinates who are likely to be monochronic in their approach to work. In addtition, the institution should device and adopt a means of communication which is low context in nature to correspond with the monochronic tendencies of the workers. Received: 25 November 2022 / Accepted: 30 December 2022 / Published: 6 March 2023